The influence of chlorhexidine gluconate and povidone iodine on the minimum inhibitory cencentration and quantitative of streptococcus mutans - Anie Apriani; Henry Yonatan Mandalas; Calvin Kurnia; Dicha Yuliadewi Rahmawati; Thio Lison; Nabila Mulyadi (Odonto : Dental Journal, 2025)
Background: An imbalance in the normal flora of the oral cavity can cause dental caries. The prevalence of caries in primary teeth in Indonesia which experiences caries is 90.2%, which shows that the prevalence of caries is still quite high. One way to prevent bacterial activity is using mouthwash. Chlorhexidine gluconate and Povidone Iodine are antibacterial agents that are effective in inhibiting bacterial growth, through bacteriostatic and bactericidal actions. This study aims to determine whether there is an inhibitory effect of chlorhexidine gluconate and povidone iodine on the growth of Streptococcus mutans (quantity).Method: This study used the broth microdilution method by treating Streptococcus mutans using  0.1 % chlorhexidine gluconate and  1% povidone iodine. The effect of inhibitory power was measured using the broth microdilution technique and the total plate count technique in the form of Colony Forming Units (CFU). Statistical calculations use the Shapiro-Wilk normality test, Levene's homogeneity test and Tukey's Post Hoc test to determine differences between treatments.Result: The results of the research showed that the treatment group in the form of 0.1% chlorhexidine gluconate and 1% povidone iodine had a very significant effect on the growth of bacterial colonies, which was very significant for the growth of Streptococcus mutans bacterial colonies.Conclusion: Chlorhexidine gluconate 0.1% and povidone iodine 1% were effective in reducing the growth of Streptococcus mutans bacteria.